The rising tide of piracy: the influence of social roles, risks and norms on illegal consumption - Whitman, Kate M.; Cox, Joe (Frontiers in Behavioral Economics, 2025)
Digital piracy, including unauthorized access to entertainment content, continues to rise, yet traditional deterrence messages often fail. Research shows that men tend to pirate more than women, but it remains unclear whether gendered social factors contribute to this disparity. Informed by Social Role Theory, we examine social deterrents to piracy by gender, focusing on perceived social risk and social norms. First, we measure illegal content consumption by gender, controlling for differences in legal demand, and evaluate the role of perceived social risk. Results show that across both music and live sports, men accessed nearly twice the proportion of their total content illegally compared to women. Perceived social risks had no effect on music piracy for either gender, but was associated with reduced piracy among men but not women in the live sports context, possibly due to the male-oriented group dynamics of sports culture. Second, we test whether a normative intervention can deter piracy intentions. Using government data to correct participants' misperceptions of the social norm (false consensus), a controlled experiment measured changes in intentions pre to post intervention. The corrected social norm did not reduce intentions to engage in piracy for those who had overestimated its prevalence but, among men who underestimated others' piracy, it backfired, increasing their piracy intentions. These findings suggest that for private, self serving behaviors, norm messaging may justify rather than deter offending. Instead, it may be more effective for interventions to emphasize piracy's reputational cost, reframing it as low-status and socially discrediting.